The (ViPER) Virtual Project Environment for Research Taxonomy - Basiel, Anthony 'Skip' (Proceedings of the International Conference on Networked Learning, 2002)
The PROS (Promoting Researchers Online Supervision) project aims to provide the necessary resources and tools to support the online supervision process for projects and research. One of the objectives is to develop a mediation tool to aid the instructional designer and the subject matter expert during the conversion process of traditional face-to-face teaching to web-based delivery and collaboration.